1983
DOI: 10.1111/j.1365-2621.1983.tb14954.x
|View full text |Cite
|
Sign up to set email alerts
|

Tannin in Common Beans: Methods of Analysis and Effects on Protein Quality

Abstract: Condensed tannins and related phenols in 13 samples of red Guatamalan common beans (Phaseolus vulgaris) were determined by four chemical assays. The results were highly correlated although the degree of variation among the samples differed greatly according to the assay. In rat feeding trials, tannin content was negatively correlated with net protein ratio, a measure of protein quality, and positively correlated with protein digestibility. Neither correlation was statistically significant due primarily to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1
2

Year Published

1988
1988
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 15 publications
3
32
1
2
Order By: Relevance
“…The influence of tea decoction on body weight growth is not con firmed by other studies. However, it has been noted that high concentration of tannins re duced growth rate in rats [16]. Also, it has been reported that mice fed with a diet con taining 5 g/100 g tannic acid had decreased mean body weight when compared with mice fed with a control diet [17], Joslyn and Glick [18] reported that feeding tannic acid to rats at 5 g/100 g diet resulted in lower weight gain (about 50% of the control).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of tea decoction on body weight growth is not con firmed by other studies. However, it has been noted that high concentration of tannins re duced growth rate in rats [16]. Also, it has been reported that mice fed with a diet con taining 5 g/100 g tannic acid had decreased mean body weight when compared with mice fed with a control diet [17], Joslyn and Glick [18] reported that feeding tannic acid to rats at 5 g/100 g diet resulted in lower weight gain (about 50% of the control).…”
Section: Discussionmentioning
confidence: 99%
“…0.0171. and 0.057g/lOOg diet) did not significantly change the body weight [12], On the basis of these findings, our data suggest that the tea decoction which is considered to be an impor tant source of tannins constitutes an impor tant factor able to reduce body weight gains in rats. This effect was not due to the difference in food intakes which were controlled, but it could be related to the influence of tannins from tea decocation on nitrogen and protein digestibility [16], In order to isolate the specific effect of the tea decoction on the trace element retention in the blood and different tissues, all results are given in a constant volume of blood (gg/ ml) and in a constant dry weight of organs (gg/g dry weight) in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that the ability to inhibit the activity of a-amylases is also attributed to phenolic compounds [2,4]. This study undertook to determine the inhibiting ability of both the named compound groups.…”
Section: A-amylase Inhibitorsmentioning
confidence: 99%
“…A favourable influence on health was also shown in the case of a-amylases, i. e., they contribute to the limitation of a postprandial increase in the concentration of glucose in blood, which alleviates the course of insulin-dependent diabetes [3]. Ability to form bonds with enzymes is also shown by phenolic compounds, tannin in particular [2,[4][5][6]. Moreover, these compounds are attributed with numerous medicinal properties which result in many cases from their strong antioxidant properties [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…Since legumes are generally deficient in sulphur containing amino acids, any impairment in the digestibility of the protein further serves to accentuate this deficiency [4]. As a complement to this view, even if all heat-labile antinutritional factors in legumes are completely removed, the effects of the heat-stable ones, especially phytic and tannic acids, on protein quality and digestibility are substantial [5,6]. Poor digestibility and biological utilization of legume protein from cooked samples have been directly related to the tannin content of these legumes [7].…”
Section: Introductionmentioning
confidence: 99%